Pendampingan Program Identifikasi Usaha Mikro, Kecil yang Berada di sekitar Kampus UOGP Kotaraja Kota Jayapura - Jonathan Karay; Yakomina Flora Hosio; Aksamina Maria Wandamo; Maikel Walilo, Septer Waran; Habel Mambraku (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2024)
Some common problems with micro businesses are capital issues, where micro business actors may have many business ideas to develop their business but have to stop because there is no additional capital. Apart from the problem of lack of capital, micro and small businesses also still do not have training for bookkeeping, and other problems in business development to increase capital and services. This PKM activity consists of three main stages: preparation stage, implementation stage and evaluation stage. The preparation stage is the initial stage carried out before starting PKM activities. The researcher added that the availability of capital is low because with the phenomenon of business results today there is no separation between business capital and profits, so sometimes the availability of capital will depend on money or personal capital again. And the problem is that additional capital is really needed for micro businesses around campus.